Examining patterns of student participation in online discussion boards - Hoekman, Annie (Kansas State University, 2017)
This research examined the nature of the patterns of communication of discussion board users who were enrolled in undergraduate level online courses. For purpose of analysis, this study used Norman Fairclough’s Critical Discourse Analysis (CDA) framework (1992). Data were collected from discussion board posts of eight undergraduate online courses that were offered by a small, private, religiously-affiliated, liberal arts university. An examination of these data was further informed by Garrison, Anderson, & Archer (1999) Community of Inquiry model. Using Garrison et al.’s ideas, the researcher described the nature of the interactions between students and faculty with respect to social, cognitive, and teaching presence in online discussion boards. The findings of this research suggest that understanding the presence of social, cognitive, and teaching presence as well as the nature of the patterns of communication in the discourse is important in developing quality distance education discussion boards. More specifically, they showed that evidence of social and teaching presence was regularly present in an examination of the online discussion boards. Conversely, the data showed very few examples of cognitive presence. Based upon the findings of this research, ideas for how constituents of online education can continue with and improve upon the practices found here relative to social and teaching presence as well as how to re-envision and improve upon cognitive presence and overall-intention for discussion boards were also offered.
Keywords: critical discourse analysis; power relationships; discussion boards; community of inquiry; online courses; undergraduate